A macroeconomic model of CETA's impact on Austria - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2017)
The Comprehensive Economic and Trade Agreement (CETA) between the European Union and Canada is the most ambitious (new generation) free trade agreement the EU has ever negotiated. It is a "mixed" agreement with EU and member countries competences. Most elements of the agreement for which the EU has "exclusive competence", including the chapter on tariffs and non-tariff barriers (the dismantling of all barriers to trade in goods and services and market access to foreign direct investment) can - after the European Parliament gave its consent on 15 February 2017 - be applied provisionally in spring 2017. With a specifically constructed macroeconomic trade and growth model for Austria, we simulate the impact of CETA on Austria. CETA will add 0.3 percent to Austria's real GDP in the medium run and will stimulate bilateral trade and FDI. Our model is a small prototype model and can easily be applied to other foreign trade agreements the EU is planning. A comparison shows that TTIP - which is "politically" dead now - would have the biggest impact (real GDP +1.7 percent).The almost finished negotiated EU-Japan foreign trade agreement would result in an increase of Austria's real GDP by 0.4 percent in the medium run.
Keywords: F10; F14; F15; F17; 330; Free trade agreement; European Union; open-economy macroeconomics